2006 Florida Plant Disease Management Guide: Avocado (Persea americana) - Aaron J. Palmateer; Randy C. Ploetz; Philip F. Harmon (EDIS, 2006)
PP-233, a 10-page illustrated publication by Aaron J. Palmateer, Randy C. Ploetz, and Philip F. Harmon, is a section of the 2006 Plant Disease Management Guide. The authors describe several important diseases of avocado in Florida, their symptoms and causal organisms, disease cycle and epidemiology, and management. Includes a table of fungicides registered for use on avocado in Florida. Published October 2006.